High-brightness flaky α-alumina powder and its manufacturing method

By firing a mixture of flaky boehmite powder and specific additives, the method enhances the average particle size and aspect ratio of flaky α-alumina powder, overcoming conventional limitations and achieving superior brightness for use as high-luminance pigments.

JP7655456B2Active Publication Date: 2025-04-02NIPPON LIGHT METAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024565852
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-19
Filing Date
2023-12-13
Publication Date
2025-04-02
Estimated Expiration
2043-12-13

AI Technical Summary

Technical Problem

Conventional flaky α-alumina powders face limitations in increasing their average particle size and aspect ratio, which restricts their brightness potential as high-luminance pigments.

Method used

A method involving the firing of a raw material mixture containing flaky boehmite powder and specific additives at temperatures between 1000°C and 1300°C, resulting in a high-brightness flaky α-alumina powder with enhanced average particle diameter and aspect ratio.

Benefits of technology

The method produces alumina powder with significantly improved brightness, as evidenced by higher brightness intensity Si values, and is achieved through a simple and cost-effective production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655456000005
    Figure 0007655456000005
  • Figure 0007655456000006
    Figure 0007655456000006
  • Figure 0007655456000007
    Figure 0007655456000007
Patent Text Reader

Abstract

Provided is a scaly α-alumina powder having a large average particle diameter and aspect ratio as well as excellent perceived luminosity, and a production method capable of obtaining the scaly alumina powder by a simple technique. This high-luminance scaly α-alumina powder has an average particle diameter of 20 μm to 200 μm, an average thickness of 0.20 μm to 2.00 μm, and an average aspect ratio of 50 to 600. Also, a perceived luminosity measurement reveals that the luminosity intensity Si at a measurement angle θ of 15° and 45° falls in the range from 1.00 to 15.00.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-brightness flaky α-alumina powder and a method for producing the same. [Background technology]

[0002] α-alumina (Al2O3) is chemically stable and has excellent heat resistance, corrosion resistance, wear resistance, and insulation properties, as well as high strength and hardness. Taking advantage of these characteristics, α-alumina powder is widely used in a variety of applications, including structural members, tools, abrasives, fillers, spark plugs, insulators, electronic substrates, and refractories.

[0003] In particular, scaly α-alumina powder has high light reflectance and brightness on its particle surface. Therefore, taking advantage of this characteristic, it is used as a high-brightness pigment added to paints and cosmetics. In addition, for pigment applications, inorganic coatings made of TiO2 and the like are applied to the particle surfaces of scaly α-alumina powder. The coating causes light interference, and it is said that this interference can be used to increase gloss.

[0004] Furthermore, flaky α-alumina powder has high strength and excellent gas barrier properties. Therefore, it is used as a reinforcing material or gas barrier material added to plastics and resin films. Note that flaky α-alumina powder is a powder composed of flaky α-alumina particles, and is also called flaky alumina powder, flat alumina powder, plate-like alumina powder, or alumina flakes.

[0005] In Patent Document 1, a thickness of 500 nm or more and a D of 15 to 30 μm are 50 value and D of 30 to 45 μm 90It is disclosed that Al2O3 flakes having a value of 0.1 to 1.0, which simultaneously have high chemical stability, a smooth surface, and high whiteness, are used as a pigment substrate (claim 1,

[0010] and

[0015] of Patent Document 1). Patent Document 1 also describes that the Al2O3 flakes are coated with a high refractive index layer such as TiO2 or a low refractive index layer such as SiO2, which gives them increased luster, interference color, or color flop effect (

[0040] to

[0046] of Patent Document 1).

[0006] Patent Document 2 discloses a paint composition containing alumina flakes as a luster pigment, and describes that it can be suitably used as an automobile topcoat paint, and that it forms a composite coating film with an unprecedented strong luster and novel designability without compromising the finished appearance (claim 1,

[0001] and

[0108] of Patent Document 2). Patent Document 2 also describes that the alumina flakes are aluminum oxide (Al2O3) coated with a metal oxide such as titanium dioxide, and have a particle size of 10 to 30 μm and a thickness of 0.3 to 0.4 μm (claim 1,

[0001] and

[0108] of Patent Document 2).

[0007] ).

[0007] Patent Document 3 discloses a pearlescent pigment containing aluminum oxide and zinc oxide as main components in a mass ratio of 100:0.1-5, and containing flaky alumina crystals coated with metal or metal precursor particles (claim 1 of Patent Document 3). Patent Document 3 also describes that the crystals have an average particle thickness of 0.5 μm or less, an average particle size of 15 μm or more, and an aspect ratio of 50 or more, and therefore have excellent gloss (

[0001] of Patent Document 3).

[0008] Patent Document 4 discloses a method for producing a plate-like alumina-based powder characterized by having a crystal structure of only α-, β-, or γ-alumina, or two or more types of crystal structures, by firing plate-like boehmite at 400° C. to 1500° C. (Claim 2 of Patent Document 4). Patent Document 4 also discloses that a cosmetic product with a good feel can be obtained by surface-coating plate-like boehmite or plate-like alumina powder with a hydrophobic compound such as polysiloxane and incorporating the coated powder into a cosmetic product (

[0013] of Patent Document 4).

[0009] Patent Document 5 discloses hexagonal plate-like alumina obtained by firing hexagonal plate-like boehmite at temperatures of 450 to 1500°C. The hexagonal plate-like alumina has a roughly hexagonal plate shape, a ratio of the major axis to the minor axis of 1 to 1.3, and an aspect ratio of 40 to 100. The document describes that the hexagonal plate-like alumina has high orientation, reduces diffuse reflection, and enhances brilliance, and can also be suitably used as a filler for the purpose of increasing the brilliance of paints and cosmetics (Claim 4 and

[0045] of Patent Document 5).

[0010] Patent Document 6 discloses plate-like alumina particles having a thickness of 0.01 to 5 μm, an average particle diameter of 0.1 to 500 μm, an aspect ratio (the ratio of the particle diameter to the thickness) of 2 to 500, a polygonal plate shape, and containing molybdenum within the particles (Claim 1 of Patent Document 6). Patent Document 6 also discloses that the plate-like alumina particles can be suitably used for thermally conductive fillers, cosmetics, abrasives, high luster pigments, lubricants, substrates for conductive powders, ceramic materials, and the like (

[0101] of Patent Document 6). [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2014-218424 A [Patent Document 2] Japanese Patent Application Publication No. 10-298458 [Patent Document 3] Special Publication No. 2010-502774 [Patent Document 4] JP 2012-071996 A [Patent Document 5] JP 2003-002642 A [Patent Document 6] JP 2019-123664 A Summary of the Invention [Problem to be solved by the invention]

[0012] Thus, in the fields of paints and cosmetics, it has been proposed to use scaly α-alumina powder as a high brightness pigment. However, the inventors have found that there is room for improvement in the conventional technology. That is, it is desirable to enhance the brilliance of alumina powder when used as a high brightness pigment. However, conventional scaly α-alumina powder has limitations in terms of increasing the reflectance of the particle surface.

[0013] In particular, it was difficult to increase the average particle size and aspect ratio of conventional scaly alumina powder. In other words, the larger the average particle size and aspect ratio, the larger the plate surface area of ​​the flat particles. Therefore, even if the surface reflectance is the same, the larger the plate surface area, the more excellent the brilliance of the alumina powder can be obtained. Conventional alumina powders had insufficient average particle size and aspect ratio, and there was a limit to increasing the brilliance.

[0014] Furthermore, as proposed in Patent Documents 1 to 3, techniques have been proposed for improving gloss by utilizing the light interference effect of inorganic coatings, but such techniques do not allow for inexpensive production of flaky α-alumina powder. In other words, after the flaky α-alumina powder is produced, it is necessary to separately form an inorganic coating such as TiO2 on the surface, which may increase production costs.

[0015] In view of the above-mentioned problems, the present inventors have conducted extensive research and have found that scaly α-alumina powder can be obtained by a simple method of firing a raw material mixture containing scaly boehmite powder and a predetermined composition of additives, and that the obtained scaly α-alumina powder has a large average particle size and aspect ratio as well as excellent brilliance.

[0016] The present invention was completed based on these findings, and an objective of the present invention is to provide a flaky α-alumina powder that has a large average particle size, a large aspect ratio, and excellent luster, and a manufacturing method for obtaining this flaky α-alumina powder by a simple technique. [Means for solving the problem]

[0017] The present invention encompasses the following embodiments (1) to (13). In this specification, the expression "to" includes both ends of the numerical value. In other words, "X to Y" is synonymous with "X or more and Y or less." In this specification, any combination of suitable embodiments can be adopted as long as technical consistency can be achieved. For example, one of the suitable numerical ranges can be combined with the other.

[0018] (1) The average particle size is 20 μm or more and 200 μm or less, the average thickness is 0.20 μm or more and 2.00 μm or less, and the average aspect ratio is 50 or more and 600 or less, A high-brightness flaky α-alumina powder having a brilliance intensity Si value in a brilliance measurement at measurement angles θ of 15° and 45° in the range of 1.00 or more and 15.00 or less.

[0019] (2) The high-brightness flaky α-alumina powder according to (1) above, wherein the average particle size is from 20 μm to 120 μm, and the average thickness is from 0.20 μm to 0.50 μm.

[0020] (3) The high-brightness flaky α-alumina powder according to (1) or (2) above, containing an alkali metal (AM) in an amount of 0.2% by mass or more and 5.0% by mass or less, calculated as AM2O, and containing silicon (Si) in an amount of 0.3% by mass or more and 10.0% by mass or less, calculated as SiO2.

[0021] (4) The high-brightness flaky α-alumina powder according to (3) above, wherein the alkali metal (AM) is sodium (Na) and / or potassium (K).

[0022] (5) The high-brightness flaky α-alumina powder according to any one of (1) to (4) above, wherein the average particle size is from 50 μm to 120 μm.

[0023] (6) The high-brightness flaky α-alumina powder according to any one of (1) to (5) above, wherein the luminous intensity Si value is within the range of 5.00 or more and 15.00 or less.

[0024] (7) A method for producing a high-brightness flaky α-alumina powder according to any one of (1) to (6), comprising the steps of: Adding additives to the scaly boehmite powder and then mixing to prepare a raw material mixture; Firing the raw material mixture at a temperature in the range of 1000° C. to 1300° C.; Equipped with The raw material mixture contains alkali metal (AM) in an amount of 0.5% by mass or more and 10.0% by mass or less, calculated as AM2O, silicon (Si) in an amount of 0.1% by mass or more and 10.0% by mass or less, calculated as SiO2, and fluorine (F) in an amount of 0.1% by mass or more and 5.0% by mass or less.

[0025] (8) The method according to (7) above, wherein the scaly boehmite powder has an average particle size of 2 μm or more and 15 μm or less and an average aspect ratio of 20 or more and 60 or less.

[0026] (9) The method according to (7) or (8) above, wherein the additive comprises aluminum fluoride (AlF3) and silicon oxide (SiO2).

[0027] (10) The method according to (9) above, wherein the additive further comprises an oxide (AM2O) and / or a carbonate (AM2CO3) of an alkali metal (AM).

[0028] (11) The method according to (7) or (8) above, wherein the additive comprises an alkali silicofluoride (AM2SiF6).

[0029] (12) The method according to any one of (7) to (11) above, wherein the alkali metal (AM) is sodium (Na) and / or potassium (K).

[0030] (13) A paint or cosmetic comprising the high-brightness flaky α-alumina powder according to any one of (1) to (6) above. Effect of the Invention

[0031] According to the present invention, there are provided a flaky α-alumina powder having a large average particle size, a large aspect ratio and excellent luster, and a production method by which this flaky α-alumina powder can be obtained in a simple manner. [Brief description of the drawings]

[0032] [Figure 1] The mechanism by which flaky α-alumina powder creates a shiny appearance is shown. [Diagram 2] 1 is a diagram for explaining a glitter evaluation method. [Diagram 3] 1 is a diagram for explaining a glitter evaluation method. [Figure 4] 1 shows an SEM image of the flaky α-alumina powder (Example 1). [Diagram 5] 1 shows an SEM image of the flaky α-alumina powder (Example 3). [Figure 6] 1 shows an SEM image of the flaky α-alumina powder (Example 3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] A specific embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described. Note that the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention.

[0034] <<1. High-brightness flake-like α-alumina powder>> The high-brightness flaky α-alumina powder of this embodiment (hereinafter, sometimes simply referred to as "α-alumina powder" or "alumina powder") is a powder containing α-alumina (Al2O3) as a main component. α-alumina has trigonal corundum crystals, and has excellent chemical stability, heat resistance, corrosion resistance, wear resistance, and insulation, and has high strength and hardness. It also has high light reflectance, brightness, and whiteness. The alumina powder of this embodiment can fully utilize these characteristics. In this specification, powder means an aggregate of many independent particles. That is, a large number of particles are aggregated to form a powder. Since each of the particles that constitute the powder is independent, the powder as a whole exhibits fluidity. It is sufficient that the majority of the particles that constitute the powder are independent. As long as the powder as a whole exhibits fluidity, some of the particles may be bonded to form an aggregate.

[0035] The alumina powder of this embodiment may contain other components as long as it contains α-alumina as the main component. However, in order to utilize the effects based on α-alumina, the content of α-alumina is preferably high. The content of α-alumina is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more. The content of α-alumina can be evaluated by determining the amount of components in the alumina powder by fluorescent X-ray analysis.

[0036] In the alumina powder of this embodiment, the particles constituting the alumina powder have a scaly (thin, flat, plate-like) shape. That is, each particle has a large plate surface and a small plate thickness. Specifically, the alumina powder has an average particle diameter of 20 μm to 200 μm, an average thickness of 0.20 μm to 2.00 μm, and an average aspect ratio of 50 to 600. Here, the average particle diameter and average thickness are the average values ​​of the particle diameter and thickness of each particle constituting the alumina powder based on the number of particles. The particle diameter is the long diameter of the particle. That is, the longest diameter of the particle plate surface is the particle diameter. The thickness is the plate thickness of the plate surface. The average aspect ratio is the ratio of the average particle diameter to the average thickness (average particle diameter / average thickness). The particle diameter, thickness, and aspect ratio can be obtained by observing the particles constituting the alumina powder with a scanning electron microscope (SEM).

[0037] By increasing the particle diameter (long diameter) and aspect ratio, it is possible to increase the brilliance of the alumina powder. This point will be explained with reference to Figure 1. As shown in Figure 1, when a powder with a high aspect ratio is molded onto a substrate by a method such as coating, the large particle plate surface is likely to be oriented so that it is aligned parallel to the substrate surface. The larger the particle diameter, the larger the surface area of ​​the particle plate surface that is aligned parallel to the substrate surface. Furthermore, light incident from the outside is reflected by the particle plate surface and radiated to the outside as reflected light. Therefore, the larger the particle diameter and aspect ratio, the easier it is for the incident light to be reflected by the particle plate surface, resulting in a higher visual brilliance.

[0038] The larger the particle size and aspect ratio, the higher the brilliance of the alumina powder. If the average particle size is less than 20 μm, the average thickness is more than 2.00 μm, or the average aspect ratio is less than 50, the brilliance of the alumina powder is insufficient. On the other hand, it is difficult to manufacture alumina powder with an average particle size of more than 200 μm, an average thickness of less than 0.20 μm, or an average aspect ratio of more than 600. In addition, the strength is low and handling is difficult. The average particle size is preferably 50 μm or more and 120 μm or less, more preferably 70 μm or more and 120 μm or less, and even more preferably 90 μm or more and 120 μm or less. The average thickness is preferably 0.20 μm or more and 0.40 μm or less, and more preferably 0.20 μm or more and 0.30 μm or less. The average particle size is preferably 20 μm or more and 120 μm or less, and the average thickness is preferably 0.20 μm or more and 0.50 μm or less. The average aspect ratio is preferably 150 or more and 600 or less, and more preferably 250 or more and 600 or less.

[0039] It is not necessary that all particles constituting the alumina powder are flaky, and the alumina powder may contain particles having shapes other than flaky, as long as the alumina powder as a whole satisfies the above-mentioned requirements for the average particle size, average thickness, and average aspect ratio.

[0040] In the high brightness flaky α-alumina powder of this embodiment, the glitter intensity Si value at measurement angles θ of 15° and 45° is in the range of 1.00 to 15.00 in the glitter measurement. Here, the glitter intensity Si is a value obtained in the glitter evaluation described later, and is an index showing the intensity of luminance based on the bright spots of the sample (alumina powder). The higher the glitter intensity Si value, the higher the glitter of the alumina powder. If the glitter intensity Si value is less than 1.00, the glitter of the alumina powder is insufficient. In addition, it is difficult to manufacture alumina powder with a glitter intensity Si value exceeding 15.00. The glitter intensity Si value is preferably 5.00 to 15.00, more preferably 7.00 to 15.00.

[0041] Preferably, the luminous area Sa value at measurement angles θ of 15° and 45° is 1.00 or more and 30.00 or less. The luminous area Sa is a value determined during luminous evaluation, and is an index showing the size of each bright spot of the sample (alumina powder). The luminous area Sa value is more preferably 10.00 or more and 30.00 or less, and even more preferably 15.00 or more and 30.00 or less.

[0042] The glitteriness of alumina powder can be evaluated using a multi-angle colorimeter, glitteriness, and particle feel meter (BYK, BYK-mac i). The evaluation method is explained with reference to Figures 2 and 3. When measuring, first put a full amount of sample (alumina powder) into the sample holder attached to the device. Then, set the sample holder with the sample in it into the device and perform the measurement. The device has a CCD chip on the extension of the vertical axis to the measurement surface of the sample holder. A light source is also provided at a position separated from the vertical axis by a predetermined measurement angle θ. As shown in Figure 2, during measurement, light is incident from the light source toward the sample, and after being reflected and scattered on the measurement surface, it enters the CCD chip. The light intensity of the reflected and scattered light incident on the CCD chip is measured and analyzed to obtain image data. As shown in Figure 3, a large number of bright spots based on each particle that constitutes the sample (alumina powder) are observed in the image data. The glitteriness intensity Si value and glitteriness area Sa value can be obtained by analyzing and quantifying the obtained image data.

[0043] The high brightness flaky α-alumina powder of the present embodiment preferably contains an alkali metal (AM) in an amount of 0.2% by mass or more and 5.0% by mass or less in terms of AM2O, and contains silicon (Si) in an amount of 0.3% by mass or more and 10.0% by mass or less in terms of SiO2. The content of the alkali metal (AM) is more preferably 0.2% by mass or more and 2.0% by mass or less in terms of AM2O, and even more preferably 0.2% by mass or more and 1.0% by mass or less in terms of SiO2. The content of silicon (Si) is more preferably 0.5% by mass or more and 3.0% by mass or less in terms of SiO2. The alkali metal (AM) is preferably at least one selected from the group consisting of sodium (Na) and / or potassium (K), that is, sodium (Na) and potassium (K). By including these components, it is possible to further enhance the brilliance of the alumina powder.

[0044] To explain this point, as described later, alkali metals (AM) and silicon (Si) are components contained in the raw material mixture during the production of alumina powder, and become liquid during firing. When the composition of the liquid phase components is appropriately controlled, the crystallization, grain growth, and surface smoothing of the alumina particles are promoted. This makes it possible to obtain alumina powder with a large average particle size and aspect ratio, a smooth particle surface, and excellent brilliance.

[0045] Furthermore, the alkali metal oxides (AM2O) and silicon oxide (SiO2) contained in the alumina powder themselves have the effect of enhancing the brilliance of the alumina powder. In other words, the liquid phase components generated during the firing process when manufacturing the alumina powder segregate as a different phase such as glass on the particle surface and / or inside the alumina powder after production. The different phases (glass phase, etc.) have a different refractive index from alumina. Therefore, it is speculated that the presence of such different phases strengthens the reflection and scattering of light incident from the outside, resulting in an enhanced brilliance.

[0046] In this way, by controlling the average particle size and aspect ratio and appropriately adjusting the amount of alkali metal (AM) and silicon (Si), it is possible to further enhance the brilliance of the alumina powder. On the other hand, if the amount of alkali metal and silicon are inappropriate, the brilliance may decrease.

[0047] The high brightness flaky α-alumina powder of the present embodiment contains at least aluminum (Al), alkali metal (AM), silicon (Si), and oxygen (O) as essential components (elements). However, as long as the above-mentioned requirements are satisfied, other components (elements) than the essential components (Al, AM, Si, O) may be contained. Furthermore, the presence of impurities that are inevitably mixed in during the manufacturing process is permitted. One such other component is fluorine (F). Among these, fluorine (F) is a component derived from an additive added during the manufacture of the alumina powder. That is, as described later, the additive added during the manufacture of the alumina powder contains fluorine (F). Most of the fluorine volatilizes during the firing process, but some may remain. The amount of fluorine in the alumina powder is typically 0.5% by mass or less, 0.3% by mass or less, or 0.1% by mass or less.

[0048] Furthermore, if other components are contained in large amounts, the brilliance of the alumina powder may be impaired. Therefore, the content of components other than the essential components (Al, AM, Si, O) is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 1 mass% or less, particularly preferably 0.5 mass% or less, and most preferably 0.1 mass% or less. In particular, since iron (Fe) has the effect of coloring the alumina powder, it is preferable to suppress its content. Preferably, the content of iron (Fe) is 0.05 mass% or less calculated as iron oxide (Fe2O3).

[0049] The specific surface area (S BET ) is 0.1m 2 / g or more 5.0m 2 / g or less is preferable, and 0.5m 2 / g or more 2.0m 2 / g or less is more preferable. If the specific surface area is too large, the particle size of the alumina powder becomes small, which may reduce the sense of brilliance. On the other hand, it is difficult to produce a scaly α-alumina powder with a small specific surface area.

[0050] The high-brightness flaky α-alumina powder of this embodiment is preferably composed of a polycrystalline body. That is, each particle constituting the alumina powder is in a polycrystalline state. By forming it into a polycrystalline body, it is possible to further enhance the brilliance of the alumina powder. Although the details of the reason for this are unclear, it is speculated that this is because silicate (AM2SiO3) is produced by the essential components (AM, Si, O), which promotes the fusion and adhesion of the alumina particles to each other, thereby causing them to become polycrystalline.

[0051] The high-brightness flaky α-alumina powder of this embodiment has high chemical stability because it is mainly composed of α-alumina. In addition, it has a large average particle size and aspect ratio, and is characterized by excellent brilliance. α-alumina powder with such characteristics is suitable for use in the fields of paints and cosmetics. However, the α-alumina powder of this embodiment is not limited to those used in paints and cosmetics. It can be applied to known applications such as reinforcing materials and gas barrier materials mixed into plastics and resin films, structural members, tools, abrasives, fillers, spark plugs, insulators, electronic substrates, and refractories.

[0052] <<2. Method for producing high-brightness flaky α-alumina powder>> The manufacturing method of the high brightness scaly α-alumina powder of this embodiment is not limited as long as it satisfies the above-mentioned requirements. However, it is preferably manufactured by the following procedure. A preferred manufacturing method includes a step of adding additives to scaly boehmite powder and then mixing them to prepare a raw material mixture (raw material mixing step), and a step of firing the raw material mixture at a temperature in the range of 1000°C to 1300°C (firing step). If necessary, a post-treatment step may be provided after the firing step. The raw material mixture contains an alkali metal (AM) in an amount of 0.5% to 10.0% by mass calculated as AM2O, silicon (Si) in an amount of 0.1% to 10.0% by mass calculated as SiO2, and fluorine (F) in an amount of 0.1% to 5.0% by mass. Each step will be described in detail below.

[0053] <Raw material mixing process> In the raw material mixing process, additives are added to scaly boehmite powder (hereinafter, sometimes simply referred to as "boehmite powder") and then mixed to prepare a raw material mixture. Scaly boehmite powder is a scaly powder whose main component is boehmite (AlOOH), which is an alumina monohydrate, and is an aluminum source for alumina powder. By using scaly boehmite powder as a raw material, alumina powder with a large average particle size and aspect ratio can be obtained. That is, in the subsequent firing process, boehmite transforms into α-alumina via intermediate alumina. When scaly boehmite powder is used as a raw material, the particle shape is inherited, so that scaly α-alumina powder can be obtained.

[0054] The size of the boehmite powder is not particularly limited as long as the alumina powder of the present embodiment can be obtained. However, the average particle size is preferably 2 μm or more and 15 μm or less, and the average aspect ratio is preferably 20 or more and 60 or less. By using the boehmite powder having such a size, the alumina powder of the present embodiment can be easily obtained. In addition, the manufacturing method of the boehmite powder having such a size is known and it is easily available. For example, Patent Document 5 discloses a manufacturing method of hexagonal plate-shaped boehmite by adding aluminum hydroxide and boric acid to a pH adjuster such as sodium hydroxide and subjecting them to a hydrothermal treatment, and the obtained hexagonal plate-shaped boehmite is said to have an outer diameter size of 0.7 to 15.0 μm and an aspect ratio of 40 to 100 (claim 2,

[0017] and

[0018] of Patent Document 5).

[0055] The additives are components that become liquid in the subsequent firing process and act as mineralizers. The additives contain at least silicon (Si) and fluorine (F), and may further contain an alkali metal (AM) as necessary. As described below, when the composition of the liquid phase components is appropriately controlled, the crystallization, grain growth, and surface smoothing of the alumina particles are promoted, and as a result, it is possible to obtain an alumina powder that has a large average particle size and aspect ratio, a smooth particle surface, and excellent brilliance. In addition, the liquid phase components exist as a different phase such as glass in the alumina powder after production, and have the effect of further enhancing the brilliance.

[0056] Therefore, in order to obtain an alumina powder having a large average particle size and aspect ratio and excellent brilliance, it is important to appropriately control the composition of the raw material mixture containing additives. Specifically, the composition of the additives is adjusted so that the raw material mixture contains an alkali metal (AM) of 0.5 mass% to 10.0 mass% in terms of AM2O, silicon (Si) of 0.1 mass% to 10.0 mass% in terms of SiO2, and fluorine (F) of 0.1 mass% to 5.0 mass%. When the composition of the raw material mixture is within the above-mentioned range, an alumina powder having a large average particle size and aspect ratio and excellent brilliance can be obtained. On the other hand, when the raw material mixture composition is inappropriate, the brilliance of the alumina powder may decrease.

[0057] The amount of alkali metal (AM) in the raw material mixture is more preferably 0.5% by mass to 5.0% by mass, more preferably 0.5% by mass to 3.0% by mass, calculated as AM2O. The alkali metal is preferably at least one selected from the group consisting of sodium (Na) and potassium (K). The amount of silicon (Si) in the raw material mixture is more preferably 0.5% by mass to 10.0% by mass, more preferably 1.0% by mass to 5.0% by mass, calculated as SiO2. The amount of fluorine (F) in the raw material mixture is more preferably 0.1% by mass to 5.0% by mass, more preferably 1.0% by mass to 3.0% by mass. By limiting the composition of the raw material mixture to the above-mentioned range, it is possible to further enhance the brilliance of the obtained alumina powder.

[0058] The additive contains at least silicon (Si) and fluorine (F). The additive may or may not contain an alkali metal (AM). The raw boehmite powder may contain an alkali metal (AM) as an impurity. If the amount of alkali metal in the boehmite powder is sufficient, the additive may not contain an alkali metal. However, if the amount of alkali metal in the boehmite powder is insufficient, it is preferable to add an alkali metal as an additive. Furthermore, the additive may contain aluminum (Al). If the additive contains aluminum, the aluminum is incorporated into the alumina powder during the firing process.

[0059] As long as an alumina powder having a high aspect ratio and a high sense of brilliance can be obtained, the additive may contain other components other than alkali metals (AM), silicon (Si), fluorine (F), aluminum (Al) and oxygen (O). However, if the amount of other components is excessively large, it may be difficult to obtain an alumina powder having a high sense of brilliance. Therefore, the content of other components is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and particularly preferably 1% by mass or less. The additive may not contain other components other than alkali metals (AM), silicon (Si), fluorine (F), aluminum (Al) and oxygen (O) in amounts exceeding the amount of impurities.

[0060] According to a preferred embodiment, the additive includes aluminum fluoride (AlF3) and silicon oxide (SiO2). When the amount of alkali metal in the boehmite powder is insufficient, the additive preferably further includes at least one selected from the group consisting of an oxide (AM2O) and a carbonate (AM2CO3) of an alkali metal (AM). According to another preferred embodiment, the additive includes an alkali silicon fluoride (AM2SiF6). By using an appropriate amount of these compounds (AlF3, SiO2, AM2O, AM2CO3, AM2SiF6) as additives, it is possible to reliably produce an alumina powder having a large average particle size and aspect ratio and excellent brilliance. In addition, these compounds are inexpensive and easily available. Therefore, it is possible to obtain a scaly alumina powder at a lower cost.

[0061] The boehmite powder and the additives may be mixed by a known method. The mixing may be performed in a dry manner or a wet manner. Dry mixing may be performed using a dry mixer such as an air blender, a V-type blender, a rocking blender, a Henschel mixer, or a Nauta mixer. In the case of wet mixing, a solvent such as water is added to the boehmite powder and the additives to form a slurry, and the obtained slurry is mixed using a wet mixer such as a ball mill, an attritor, or a bead mill.

[0062] <Firing process> In the firing process, the raw material mixture containing the scaly boehmite powder and additives is fired at a temperature in the range of 1000°C to 1300°C to obtain a fired product. During firing, boehmite (AlOOH) transforms into α-alumina (Al2O3), a high-temperature stable phase, via intermediate alumina such as γ-Al2O3, which is a metastable phase. Since the particle shape is maintained during the transformation, scaly α-alumina (Al2O3) is obtained. During firing, the alkali metals (AM), silicon (Si) and fluorine (F) in the raw material mixture become liquid phase in the oxide state and act as mineralizers that promote the crystallization of α-alumina. In other words, when the intermediate alumina transforms into α-Al2O3, the crystal structure changes from a cubic close-packed structure to a hexagonal close-packed structure, and oxygen in the crystal is rearranged accordingly. Therefore, the transformation into α-Al2O3 requires the addition of a certain amount of thermal energy. By adding a mineralizer, the crystallization of the α-Al2O3 crystal structure (corundum structure) is promoted, making it possible to lower the temperature of the transformation.

[0063] In addition, the mineralizer components (AM, Si, F) that become liquid during firing cover the surface of the alumina particles and some of them penetrate into the inside of the particles. This liquid phase component has the function of promoting the diffusion and growth of particles. That is, some of the aluminum atoms (Al) from the surface of the alumina particles dissolve into the liquid phase, and the dissolved aluminum precipitates in another place on the particle surface. This causes the growth of the alumina particles. At this time, depending on the composition of the liquid phase component, differences in the growth direction of the alumina particles occur and the growth rate changes. Therefore, if the composition of the liquid phase component is appropriately controlled, the growth of the alumina particles in the plate surface direction progresses significantly. The liquid phase component also has the effect of smoothing the plate surface of the alumina particles. If the alumina particle surface is uneven, the uneven parts will diffuse preferentially into the liquid phase and the uneven parts will disappear. Therefore, if the composition of the liquid phase component is appropriately controlled, it is possible to obtain alumina powder with a large average particle size and aspect ratio, a smooth particle surface, and excellent brilliance.

[0064] If the firing temperature is less than 1000°C, the transition to α-alumina and grain growth may be insufficient. Therefore, it may be difficult to obtain α-alumina powder with excellent brilliance. On the other hand, if the firing temperature is more than 1300°C, the particles may sinter together to form a strong sintered mass. In addition, the energy consumption for firing may become excessive, which may lead to an increase in manufacturing costs. The firing temperature is preferably 1000°C or more and 1200°C or less, more preferably 1000°C or more and 1100°C or less. In addition, the firing time is preferably 10 hours or more and 20 hours or less. This makes it possible to reliably ensure the transition to α-alumina and grain growth while preventing excessive sintering of the particles. The firing furnace is not limited as long as the desired alumina powder is obtained. However, from the viewpoint of effectively exerting the action of the additive during firing, a stationary furnace capable of firing using a closed firing container is preferable.

[0065] <Post-processing> If necessary, the fired product obtained through the firing process may be subjected to post-treatment such as soda removal, crushing, and / or classification. In the soda removal treatment, excess alkali metal components attached to the fired product surface are removed. This allows the amount of alkali metal in the finally obtained α-alumina powder to be adjusted. The alkali metal components on the particle surface can be removed, for example, by washing and filtering the fired product. In the crushing treatment, mild mechanical energy is applied to the fired product to break the bonds of the aggregated particles formed during firing. The crushing treatment can be performed in a dry or wet manner using a crusher such as a pot mill, a pin mill, and / or a jaw crusher. In the classification treatment, particles are selected according to size to obtain alumina powder of the desired particle size. The classification treatment can be performed by a technique such as sieving, air classification, elutriation, and / or centrifugation. The post-treatment may be performed as necessary. If the desired alumina powder can be obtained after firing, the post-treatment may be omitted.

[0066] In this manner, the scaly α-alumina powder of the present embodiment can be produced. The resulting alumina powder has a large average particle size and aspect ratio, and is excellent in luster. Therefore, it can be suitably used in various applications, including paints and cosmetics.

[0067] <<3. Paints and cosmetics>> The paint or cosmetic of this embodiment contains the high-brightness scaly α-alumina powder. The paint or cosmetic may contain the alumina powder alone or in a surface-treated form. The surface treatment may be performed by providing a surface treatment agent such as a silicon-based compound, an alkylsilane-based compound, and / or a fluorine-based compound on the particle surface of the scaly α-alumina powder. The paint or cosmetic may contain a solvent or a resin in addition to the scaly α-alumina powder. The solvent may be aqueous or non-aqueous. The paint or cosmetic may further contain known additives such as oils, pigments other than the scaly α-alumina powder, fillers, surfactants, viscosity adjusters, preservatives, fragrances, moisturizers, physiologically active ingredients, salts, chelating agents, neutralizing agents, and / or pH adjusters. EXAMPLES

[0068] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to the following examples.

[0069] (1) Preparation of alumina powder [Example 1] <Raw material mixing process> Scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-1160) was prepared as the alumina source. Aluminum fluoride (DO-FLUORIDE CHEMICALS CO., LTD.; AlF3) and silicon oxide (Marukama Kamado Toryo Co., Ltd., Yukijirushi Silica SP-3; SiO2) were also prepared as additives. The properties of the prepared scaly boehmite powder are shown in Table 1 below.

[0070] Next, 50 g of the prepared scaly boehmite powder, 1.2 g of aluminum fluoride (AlF3), and 0.4 g of silicon oxide (SiO2) were mixed to obtain a raw material mixture. The raw materials were placed in a bag and shaken to mix. The obtained raw material mixture contained 0.7 mass% sodium (Na) calculated as Na2O, 0.8 mass% silicon (Si) calculated as SiO2, and 1.6 mass% fluorine (F).

[0071] <Firing process> The obtained raw material mixture was placed in a crucible (Nikkato Corporation, SSA-H 500mL) and the crucible was closed with a special lid. This crucible had a composition of Al2O3: 95% and SiO2: 3%. Next, the crucible with the lid was placed in a firing furnace (Siliconite Corporation, box-type Siliconite electric furnace, BSH-3570) and fired in the air. During firing, the temperature was raised to 1100°C at a heating rate of 100°C / hour, and then held at 1100°C for 10 hours, and then naturally cooled. After the temperature inside the furnace had dropped, the crucible was removed from the furnace and the fired product (alumina) was collected.

[0072] <Soda removal process> The obtained calcined product (alumina) was subjected to a soda removal process. Specifically, 340 g of the calcined product was put into 7 L of pure water and mixed to form a slurry. The resulting slurry was then filtered to obtain an alumina residue. This removed the sodium content adhering to the calcined product.

[0073] <Crushing process> The obtained alumina residue was subjected to a crushing treatment. Specifically, pure water was added again to the alumina residue, and the mixture was stirred to form a slurry. The obtained slurry was placed in a pot mill container with a capacity of 10 L together with 15 kg of zirconia beads of 1 mmΦ, and the pot mill container was rotated at a rotation speed of 60 rpm for 3 hours. Next, the slurry was removed from the pot mill container and filtered to obtain a crushed product (alumina). The obtained crushed product was then dried overnight at 105°C using a dryer.

[0074] <Classification process> The crushed material obtained was subjected to classification. Specifically, pure water was added to the crushed material, and the mixture was stirred to form a slurry. The resulting slurry was then sieved using a resin mesh gyrosifter with 25 μm openings (Tokuju Machine Works, GS-A1H). The sieving was performed at a rotation speed of 60 rpm to remove coarse particles with a size of more than 25 μm. The sieve-passed material from which the coarse particles had been removed was then filtered using a SUS mesh with 12 μm openings to remove fine particles with a size of less than 12 μm. In this manner, alumina powder was produced.

[0075] [Example 2] In the raw material mixing step, 50 g of scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-1160), 1.2 g of aluminum fluoride (AlF3), and 0.6 g of silicon oxide (SiO2) were mixed to obtain a raw material mixture. The obtained raw material mixture contained 0.7 mass% sodium (Na) calculated as Na2O, 1.2 mass% silicon (Si) calculated as SiO2, and 1.6 mass% fluorine (F). In addition, soda removal and crushing were not performed, and classification was performed according to the following procedure. Alumina powder was produced in the same manner as in Example 1 except for the above.

[0076] <Classification process> The fired product (alumina) obtained in the firing process was subjected to elutriation using a sorting tube and particle size adjustment using a SUS net to remove extremely thick particles and fine particles. Specifically, pure water was added to 300 g of the fired product and then stirred to obtain a slurry with a concentration of 100 g / L. The obtained slurry was placed in a sorting device (sorting tube), and pure water was added on top at a flow rate of 1 L / min for 3 hours. The slurry containing the precipitate was then recovered from the sorting device. Next, the slurry was hand-sieved using a SUS net with a mesh size of 63 μm and a SUS net with a mesh size of 45 μm in succession, and fine particles with a size of less than 45 μm were removed from the recovered slurry. The residue obtained after hand sieving was dried overnight using a dryer.

[0077] [Example 3] In the raw material mixing step, 50 g of scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-1160), 1.2 g of aluminum fluoride (AlF3), and 0.8 g of silicon oxide (SiO2) were mixed to obtain a raw material mixture. The obtained raw material mixture contained 0.7 mass% sodium (Na) calculated as Na2O, 1.6 mass% silicon (Si) calculated as SiO2, and 1.6 mass% fluorine (F). In addition, soda removal and crushing were not performed, and classification was performed according to the following procedure. Alumina powder was produced in the same manner as in Example 1 except for the above.

[0078] <Classification process> The fired product (alumina) obtained in the firing process was subjected to elutriation using a sorting tube and particle size adjustment using a SUS mesh to remove extremely thick particles and fine particles. Specifically, pure water was added to 300 g of the fired product and then stirred to obtain a slurry with a concentration of 100 g / L. The obtained slurry was placed in a sorting device (sorting tube), and pure water was added on top at a flow rate of 1 L / min for 3 hours. The slurry containing the precipitate was then recovered from the sorting device. Next, the slurry was manually sieved using a SUS mesh with a mesh size of 45 μm, and fine particles with a size of less than 45 μm were removed from the recovered slurry. The residue obtained after manual sieving was dried overnight using a dryer.

[0079] [Example 4] In the raw material mixing step, 50 g of scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-1160), 1.2 g of aluminum fluoride (AlF3), 0.8 g of silicon oxide (SiO2), and 0.08 g of sodium carbonate (Na2CO3) were mixed to obtain a raw material mixture. The obtained raw material mixture contained 0.6 mass% sodium (Na) calculated as Na2O, 1.6 mass% silicon (Si) calculated as SiO2, and 1.6 mass% fluorine (F). In addition, soda removal and crushing were not performed, and classification was performed according to the following procedure. Alumina powder was produced in the same manner as in Example 1 except for the above.

[0080] <Classification process> The fired product (alumina) obtained in the firing process was subjected to elutriation using a sorting tube and particle size adjustment using a SUS mesh to remove extremely thick particles and fine particles. Specifically, pure water was added to 300 g of the fired product and then stirred to obtain a slurry with a concentration of 100 g / L. The obtained slurry was placed in a sorting device (sorting tube), and pure water was added on top at a flow rate of 1 L / min for 3 hours. The slurry containing the precipitate was then recovered from the sorting device. Next, the slurry was manually sieved using a SUS mesh with an opening of 63 μm, and fine particles with a size of less than 63 μm were removed from the recovered slurry. The residue obtained after manual sieving was dried overnight using a dryer.

[0081] [Example 5] In the raw material mixing step, 50 g of scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-1160) and 2.5 g of sodium silicofluoride (Na2SiF6) were mixed to obtain a raw material mixture. The obtained raw material mixture contained 0.7 mass% sodium (Na) calculated as Na2O, 1.6 mass% silicon (Si) calculated as SiO2, and 2.8 mass% fluorine (F). In addition, soda removal treatment, crushing treatment, and classification treatment were not performed. Alumina powder was produced in the same manner as in Example 1 except for the above.

[0082] [Example 6] Scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-920) was used as the alumina source. The obtained raw material mixture contained 0.6 mass% sodium (Na) calculated as Na2O, 1.6 mass% silicon (Si) calculated as SiO2, and 1.6 mass% fluorine (F). In addition, soda removal treatment, crushing treatment, and classification treatment were not performed. Alumina powder was produced in the same manner as in Example 3 except for the above.

[0083] [Example 7] In the raw material mixing step, 50 g of scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-1160), 1.2 g of aluminum fluoride (AlF3), 2.4 g of silicon oxide (SiO2), and 1.8 g of sodium carbonate (Na2CO3) were mixed to obtain a raw material mixture. The obtained raw material mixture contained 0.7 mass% sodium (Na) calculated as Na2O, 4.4 mass% silicon (Si) calculated as SiO2, and 1.5 mass% fluorine (F). In addition, soda removal treatment, crushing treatment, and classification treatment were not performed. Alumina powder was produced in the same manner as in Example 1 except for the above.

[0084] [Example 8] Scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-520) was used as the alumina source. In the raw material mixing process, 50 g of scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-520), 1.2 g of aluminum fluoride (AlF3), 4.8 g of silicon oxide (SiO2), and 1.2 g of sodium carbonate (Na2CO3) were mixed to obtain a raw material mixture. The obtained raw material mixture contained 0.6 mass% sodium (Na) calculated as Na2O, 8.4 mass% silicon (Si) calculated as SiO2, and 1.4 mass% fluorine (F). Furthermore, desoda treatment, crushing treatment, and classification treatment were not performed. Alumina powder was produced in the same manner as in Example 1 except for the above.

[0085] [Example 9] <Raw material mixing process> As the alumina source, scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-520) was used. In the raw material mixing process, the scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-520) and sodium silicofluoride (Na2SiF6) were mixed to obtain a raw material mixture containing 3.8 mass% Na2SiF6.

[0086] <Firing process> The obtained raw material mixture was placed in a sagger (KR-4A, 300mm x 300mm x 100mH, ACOCERAMIC CO., LTD.) and sealed with a special lid. The sealed sagger was then placed in a firing furnace (Siliconite Co., Ltd., box-type Siliconite electric furnace, BSH-3570) and fired in air. During firing, the temperature was raised to 1100°C at a heating rate of 100°C / hour, and then held at 1100°C for 10 hours, after which it was naturally cooled. After the temperature inside the furnace had dropped to its lowest point, the sagger was removed from the furnace and the fired product (alumina) was collected.

[0087] The recovered calcined product (alumina) was used as alumina powder, without being subjected to soda removal treatment, crushing treatment, or classification treatment.

[0088] [Example 10] <Raw material mixing process> As an alumina source, scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-920) was used. In the raw material mixing process, the scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-920) and sodium silicofluoride (Na2SiF6) were mixed to obtain a raw material mixture containing 1.3 mass% Na2SiF6.

[0089] <Firing process> The firing furnace is a shuttle kiln (Takasago Industrial Co., Ltd., 0.6m 3 A shuttle kiln (under-upper type) was used. Except for that, firing was carried out under the same conditions as in Example 9 to obtain a fired product (alumina).

[0090] <Crushing process> The obtained fired product (alumina) was subjected to a crushing treatment. Specifically, pure water was added to the fired product, and the mixture was stirred to form a slurry. The obtained slurry was placed in a pot mill container with a capacity of 10 L together with 15 kg of zirconia beads having a diameter of 1 mm, and the pot mill container was rotated at a rotation speed of 60 rpm for 3 hours. The slurry was then removed from the pot mill container to obtain a crushed product (alumina).

[0091] <Classification process> The crushed material (alumina) obtained in the crushing process was subjected to elutriation using a sorting tube and particle size adjustment using a SUS net to remove extremely thick particles and fine particles. Specifically, the slurry containing the crushed material was put into a classification device (sorting tube), and pure water was added on top at a flow rate of 1 L / min for 3 hours. The slurry containing the precipitate was then recovered from the classification device. Next, the slurry was hand sieved using a SUS net with a mesh size of 108 μm and a SUS net with a mesh size of 45 μm in succession, and fine particles with a size of less than 45 μm were removed from the recovered slurry. The residue obtained after hand sieving was dried overnight using a dryer.

[0092] [Example 11] <Raw material mixing process> Scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-920) was used as the alumina source. In the raw material mixing process, scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-920), aluminum fluoride (AlF3), silicon oxide (SiO2), and sodium carbonate (Na2CO3) were mixed to obtain a raw material mixture containing 2.7% AlF3, 1.0 mass% SiO2, and 1.7 mass% Na2CO3.

[0093] <Firing process> The obtained raw material mixture was calcined, and the calcined product (alumina) was collected. The calcination was carried out under the same conditions as in Example 10, except that the retention time was 20 hours.

[0094] The recovered calcined product (alumina) was used as alumina powder, without being subjected to soda removal treatment, crushing treatment, or classification treatment.

[0095] [Example 12] The raw materials were mixed so as to obtain a raw material mixture containing 3.1 mass% of sodium silicofluoride (Na2SiF6). The retention time during firing was set to 20 hours. Except for this, the alumina powder was produced in the same manner as in Example 10.

[0096] [Comparative Example 1] <Raw material mixing process> As an alumina source, alumina with a BET specific surface area of ​​0.8 to 1.2 m produced by rotary kiln firing was used. 2 The properties of the prepared alumina powder are shown in Table 1 below.

[0097] Next, alumina powder and silicon oxide (SiO2) were mixed to obtain a raw material mixture. Silicon oxide was added so that the amount of silicon oxide was 0.3 mass% relative to the alumina powder. Silicon oxide changes the sodium (Na) in the alumina powder into the form of sodalite in the melting process described below. Since sodalite can be removed in the pickling process, it is possible to reduce the amount of sodium in the alumina by changing it into the form of sodalite.

[0098] <Melting process> The resulting raw material mixture was subjected to arc discharge treatment in an electric arc furnace for 8 to 9 hours. During the treatment, the raw material mixture melted into a molten metal. The molten metal temperature was over 2000°C. After melting, the molten metal was cooled to obtain a molten mass.

[0099] <Crushing and grinding> The obtained molten mass was divided into pieces the size of a human head using a Powerman, and then sieved using a trommel (25 mm x 25 mm sieve). The masses larger than 25 mm remaining on the sieve were collected and crushed until particles of several tens of μm to several mm in size were obtained.

[0100] <Pickling> The obtained pulverized material was washed with a 4% sulfuric acid solution to remove sodalite generated in the molten porcelain. The washed product was filtered with a horizontal filter, dried in a kiln, and then sieved to obtain fused alumina with an average particle size of 250 to 350 μm.

[0101] <Crushing> The obtained electrofused alumina was pulverized using a continuous vibration mill to obtain an alumina powder having an average particle size of 18 μm.

[0102] [Comparative Example 2] Aluminum hydroxide A (Al(OH)3) produced by the Bayer process was prepared as the alumina source. The properties of the prepared aluminum hydroxide A are shown in Table 1 below.

[0103] <Firing> A fixed amount of prepared aluminum hydroxide A was charged into the raw material charging section of the rotary kiln calcination equipment. The moisture adhering to aluminum hydroxide A was removed in the pre-drying section of the calcination equipment, and then a fixed amount of aluminum fluoride (AlF3) was added. After that, aluminum hydroxide A with added aluminum fluoride was calcined with the calcined product. Calcination was carried out under the conditions of 1280-1380°C x 2 hours. As a result, alumina powder was obtained.

[0104] [Comparative Example 3] Imported aluminum hydroxide B (Al(OH)3) was used as the alumina source. The properties of the aluminum hydroxide B used are shown in Table 1 below. Otherwise, the alumina powder was produced in the same manner as in Comparative Example 2.

[0105] [Comparative Example 4] In the raw material mixing process, 50 g of scaly boehmite powder (Kawai Lime Industry Co., Ltd., BMF-1160) and 1.2 g of aluminum fluoride (AlF3) were mixed, but silicon oxide (SiO2) was not added. The obtained raw material mixture contained 0.7 mass% sodium (Na) calculated as Na2O, 0.02 mass% silicon (Si) calculated as SiO2, and 1.6 mass% fluorine (F). In addition, soda removal treatment, crushing treatment, and classification treatment were not performed. Alumina powder was produced in the same manner as in Example 1 except for the above.

[0106] The production conditions for the alumina powders of Examples 1 to 12 and Comparative Examples 1 to 4 are summarized in Tables 2 and 3 below.

[0107] [Table 1]

[0108] [Table 2]

[0109] [Table 3]

[0110] (2) Evaluation The alumina powders obtained in Examples 1 to 12 and Comparative Examples 1 to 4 were evaluated for various properties as follows.

[0111] <Average particle size and thickness> Evaluation was performed using a scanning electron microscope (JEOL Ltd., JSM-F100; SEM) and image analysis software (ImageJ). Specifically, an SEM image of the obtained alumina powder was taken, and the particles shown in the image were evaluated using ImageJ to measure the particle size and thickness. The average particle size was calculated as the average value of 80 particles, and the average thickness was calculated as the average value of 30 particles.

[0112] <Crystal phase> The crystal phase was evaluated using an X-ray diffractometer (Rigaku Corporation, RINT UltimaIII). Specifically, the obtained alumina powder was first placed on a dedicated sample plate and gently spread to a size of 20 mm x 20 mm x 0.5 mm to prepare a measurement sample. Next, the X-ray diffraction pattern of the measurement sample was evaluated using the X-ray diffractometer.

[0113] <Component analysis> The component analysis was performed using a scanning X-ray fluorescence analyzer (Rigaku Corporation, ZSX PrimusIV). Specifically, the obtained alumina powder was first placed in a platinum crucible and set in a high-frequency melting device. After that, the alumina powder was preheated at 700°C for 60 seconds, and then rocked at 1200°C for 120 seconds to produce a glass beaded sample. The glass bead sample was then evaluated using a scanning X-ray analyzer. The obtained data was compared with the data of the standard sample for the calibration curve to obtain the evaluation results.

[0114] <Specific surface area> The specific surface area was evaluated by N2 gas adsorption method using a manual specific surface area measuring device (Micromeritics Instrument Corp., FlowSorbIII 2305 type).

[0115] <Brilliance evaluation> The brilliance of the alumina powder was evaluated using a multi-angle colorimeter (BYK-Gardner, BYK-mac i, measurement aperture diameter: 12 mm). Specifically, a measurement sample was prepared by filling the aperture (35 mmΦ×5 mmH) of the sample holder with a full amount of alumina powder, and the measurement sample was set in the colorimeter and measured. During the measurement, a CCD chip was placed on an axis perpendicular to the measurement surface of the sample holder, and light was irradiated from a direction at an angle of 15°, 45°, or 75° from the perpendicular axis, and an image was taken with the CCD chip. The obtained image was then analyzed using an image analysis algorithm to determine the light luminance Si value and the brilliance area Sa value at each measurement angle (15°, 45°, 75°).

[0116] (3) Evaluation results The evaluation results obtained for the alumina powders obtained in Examples 1 to 12 and Comparative Examples 1 to 4 are summarized in Table 4. Moreover, SEM images of the alumina powder obtained in Example 1 are shown in Fig. 4, and SEM images of the alumina powder obtained in Example 3 are shown in Figs. 5 and 6.

[0117] As shown in Table 4, the alumina powders of Examples 1 to 12, which were produced using scaly boehmite powder and additives of a predetermined composition as raw materials, had average particle diameters, average thicknesses, and average aspect ratios within the predetermined ranges. The amounts of sodium oxide (Na2O) and silicon oxide (SiO2) also satisfied the ranges specified in this embodiment, and the brilliance intensity Si values ​​were high. In particular, as can be seen from the results of the samples of Examples 1 to 3, the brilliance intensity Si values ​​increased as the average particle diameter increased.

[0118] 4 and 5, it was found that the alumina powders of Examples 1 and 3 had a scaly shape with a large plate surface and a small plate thickness, and the surface of the plate surface was smooth. The cross-sectional SEM image and the enlarged SEM image of FIG. 6 revealed that the alumina powder of Example 3 had a polycrystalline structure.

[0119] On the other hand, in Comparative Examples 1 to 3, which were produced using alumina or aluminum hydroxide as raw materials, flat alumina powder could not be obtained. Also, the alumina powders of Comparative Examples 1 to 3 had low luminance intensity Si values. Furthermore, the alumina powder of Comparative Example 4, which used scaly boehmite powder as raw material but did not add silicon oxide (SiO2), had a small average particle size and aspect ratio, and also had a small luminance intensity Si value.

[0120] From the above results, it was found that the scaly α-alumina powder of this embodiment has a large average particle size and aspect ratio, and is excellent in brilliance.

[0121] [Table 4]

Claims

1. The average particle size is 50 μm or more and 200 μm or less, the average thickness is 0.20 μm or more and 2.00 μm or less, and the average aspect ratio is 50 or more and 600 or less, In the glitter measurement, the glitter intensity Si value at the measurement angle θ of 15° and 45° is in the range of 1.00 to 15.00, A high-brightness flake-like α-alumina powder containing an alkali metal (AM) and silicon (Si).

2. Alkali metal (AM) 2 The silicon (Si) content is 0.2 mass% or more and 5.0 mass% or less in terms of O, and the silicon (Si) content is SiO 2 The high-brightness flaky α-alumina powder according to claim 1, wherein the α-alumina powder contains 0.3% by mass or more and 10.0% by mass or less in terms of the amount of α-alumina converted into α-alumina.

3. 3. The high-brightness flaky α-alumina powder according to claim 2, wherein the alkali metal (AM) is sodium (Na) and / or potassium (K).

4. 4. The high-brightness flaky α-alumina powder according to claim 1, wherein the luminance intensity Si value is in the range of 5.00 or more and 15.00 or less.

5. A method for producing the high-brightness flaky α-alumina powder according to any one of claims 1 to 3, comprising the steps of: Adding additives to the scaly boehmite powder and then mixing to prepare a raw material mixture; Firing the raw material mixture at a temperature in the range of 1000° C. to 1300° C.; Equipped with The raw material mixture is an alkali metal (AM) 2 O equivalent of 0.5 mass% or more and 10.0 mass% or less, silicon (Si) is SiO 2 and fluorine (F) in an amount of 0.1 mass% or more and 10.0 mass% or less, calculated as carbon black or silver halide.

6. The method according to claim 5 , wherein the scaly boehmite powder has an average particle size of 2 μm or more and 15 μm or less and an average aspect ratio of 20 or more and 60 or less.

7. The additive is aluminum fluoride (AlF 3 ) and silicon oxide (SiO 2 6. The method of claim 5, comprising:

8. The additive is an oxide of an alkali metal (AM). 2 O) and / or carbonate (AM 2 CO 3 8. The method of claim 7, further comprising:

9. The additive is an alkali silicofluoride (AM 2 SiF 6 6. The method of claim 5, comprising:

10. 6. The method according to claim 5, wherein the alkali metal (AM) is sodium (Na) and / or potassium (K).

11. A paint or cosmetic comprising the high-brightness flaky α-alumina powder according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Brilliant pigment-containing coating composition and formation of composite coating film

    JP1998298458A

  • Hexagonal-plate-like boehmite, hexagonal-plate-like alumina, and method for producing them

    JP2003002642A

  • Flat alumina particle and cosmetic using the same and its manufacturing method

    JP2003192338A

  • Flaky particles, and cosmetic, coating material composition, resin composition and ink composition each blended with the same

    JP2004043291A

  • METHOD FOR PRODUCING FLAKY alpha-ALUMINA

    JP2009035430A